Seeding-Layer-Free Deposition of High-k Dielectric on CVD Graphene for Enhanced Gate Control Ability - Yunpeng Yan; Songang Peng; Zhi Jin; Dayong Zhang; Jingyuan Shi (Crystals, 2022)
The gate insulator is one of the most crucial factors determining the performance of a graphene field effect transistor (GFET). Good electrostatic control of the conduction channel by gate voltage requires thin gate oxides. Due to the lack of the dangling bond, a seed layer is usually needed for the gate dielectric film grown by the atomic layer deposition (ALD) process. The seed layer leads to the high-quality deposition of dielectric films, but it may lead to a great increase in the thickness of the final dielectric film. To address this problem, this paper proposes an improved process, where the self-oxidized Al2O3 seed layer was removed by etching solutions before atomic layer deposition, and the Al2O3 residue would provide nucleation sites on the graphene surface. Benefiting from the decreased thickness of the dielectric film, the transconductance of the GFET using this method as a top-gate dielectric film deposition process shows an average 44.7% increase compared with the GFETs using the standard Al evaporation seed layer methods.